2014
DOI: 10.1097/mca.0000000000000159
|View full text |Cite
|
Sign up to set email alerts
|

Switching types of drug-eluting stents does not prevent repeated in-stent restenosis in patients with coronary drug-eluting stent restenosis

Abstract: ObjectivesWe treated patients experiencing drug-eluting stent (DES) restenosis with plain old balloon angioplasty (POBA), implantation of the same type of DES [homogeneous drug-eluting stent (HOMO-DES)], or implantation of a different type of DES [heterogeneous drug-eluting stent (HETERO-DES)], and compared the efficacy and safety of these procedures for the prevention of repeated in-stent restenosis (ISR).BackgroundIn patients with de-novo coronary lesions, DES implantation is associated with a markedly reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The drug‐specific factors may inhibit greater formation of intimal hyperplasia in stents using different DESs when compared to that using the same DESs. Taking into account these contributing factors, several investigations have examined the treatment of DES‐ISR using different types of DES re‐implantation, but failed to show a significant improvement compared to the same type of DES . A limited paper reported by Mishkel et al demonstrated treatment with a different DES for DES‐ISR tended to result in better 12‐month outcomes than with the same DES, though it was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The drug‐specific factors may inhibit greater formation of intimal hyperplasia in stents using different DESs when compared to that using the same DESs. Taking into account these contributing factors, several investigations have examined the treatment of DES‐ISR using different types of DES re‐implantation, but failed to show a significant improvement compared to the same type of DES . A limited paper reported by Mishkel et al demonstrated treatment with a different DES for DES‐ISR tended to result in better 12‐month outcomes than with the same DES, though it was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account these contributing factors, several investigations have examined the treatment of DES-ISR using different types of DES re-implantation, but failed to show a significant improvement compared to the same type of DES. [12][13][14]23 A limited paper reported by Mishkel et al 24 demonstrated treatment with a different DES for DES-ISR tended to result in better 12-month outcomes than with the same DES, though it was not statistically significant. Most of those studies were conducted to investigate a cohort treated in the first-generation DES era.…”
Section: Discussionmentioning
confidence: 99%
“…When the DES arm was considered alone, drug-switching still showed an advantage (HR 0.35, CI 0.15-0.79, P = 0.012). However, this finding should not be considered definitive because it was not a pre-specified analysis and prior studies have produced conflicting results regarding the benefit of a drug-switching strategy [7][8][9].…”
mentioning
confidence: 94%
“…According to the institutional protocols, and as previously noted in our study methods, a switch strategy (Hetero-DES) was adopted in all cases, including those with DES re-restenosis. Nevertheless, whether or not to adopt a switch strategy in DES-associated restenosis is still a matter of debate [2], [3], even with second-generation DES [4].…”
mentioning
confidence: 99%